2008
DOI: 10.1158/0008-5472.can-07-5723
|View full text |Cite
|
Sign up to set email alerts
|

The Nucleolin Targeting Aptamer AS1411 Destabilizes Bcl-2 Messenger RNA in Human Breast Cancer Cells

Abstract: We sought to determine whether nucleolin, a bcl-2 mRNAbinding protein, has a role in the regulation of bcl-2 mRNA stability in MCF-7 and MDA-MB-231 breast cancer cells. Furthermore, we examined the efficacy of the aptamer AS1411 in targeting nucleolin and inducing bcl-2 mRNA instability and cytotoxicity in these cells. AS1411 at 5 Mmol/L inhibited the growth of MCF-7 and MDA-MB-231 cells, whereas 20 Mmol/L AS1411 had no effect on the growth rate or viability of normal MCF-10A mammary epithelial cells. This sel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
387
2
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 458 publications
(403 citation statements)
references
References 21 publications
12
387
2
2
Order By: Relevance
“…However, it is also possible that KLF4 may be migrated to cell surface under overexpression conditions. Recent studies showed that nucleolin, a nuclear protein, was present on the surface of various cell types, despite lacking a transmembrane domain or a signal sequence (24,25). Therefore, nucleolin acts as a receptor on plasma membrane and shuttles the ligand from the plasma membrane to the cytoplasm and nucleus (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also possible that KLF4 may be migrated to cell surface under overexpression conditions. Recent studies showed that nucleolin, a nuclear protein, was present on the surface of various cell types, despite lacking a transmembrane domain or a signal sequence (24,25). Therefore, nucleolin acts as a receptor on plasma membrane and shuttles the ligand from the plasma membrane to the cytoplasm and nucleus (24,26).…”
Section: Discussionmentioning
confidence: 99%
“…133,134 AS1411 may directly inhibit the RNA-binding activity of nucleolin, as AS1411 reduced nucleolin binding to BCL2 mRNA resulting in BCL2 mRNA destabilization, decreased Bcl-2 protein levels, apoptotic death of cultured human breast cancer cells, and inhibition of cancer cell growth in xenografts. 135,136 Other effects of AS1411 include the inhibition of NFκB via the formation of a complex containing nucleolin and the NFκB essential modulator (NEMO). 137 Cell-surface nucleolin mediates the effects of this aptamer through binding and internalization leading to inhibition of cell growth.…”
Section: Targeting Nucleolin For Therapymentioning
confidence: 99%
“…The role of nucleolin in these pathological processes roots from its function(s) in DNA metabolism, chromatin re-modeling, ribosome biogenesis and mRNA decay (23). Nucleolin has been found to bind to the mRNA of several important genes, including p53 (24), bcl-2 (25), and bcl-xl (26), leading to regulation on mRNA turnover or translation. Moreover, nucleolin has been shown to have binding activity to a number of G-rich oligonucleotides, like the G-quadruplex structure in the promoter region of c-myc gene (27) and vegf gene (28).…”
mentioning
confidence: 99%